2012
DOI: 10.1016/j.neuro.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of neurobehavioral effects of methylmercury exposure in older and younger adult zebrafish (Danio rerio)

Abstract: It is widely recognized that the nature and severity of responses to toxic exposure are age-dependent. Using active avoidance conditioning as the behavioral paradigm, the present study examined the effect of short-term methylmercury (MeHg) exposure on two adult age classes, 1- and 2-year-olds to coincide with zebrafish in relatively peak vs. declining health conditions. In Experiment 1, 2-year-old zebrafish were randomly divided into groups and were exposed to no MeHg, 0.15% ethanol (EtOH), 0.01, 0.03, 0.1, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…We used the zebrafish model to investigate the toxicity of the individual PAHs compared to the SM10 mixture in developing larvae and to evaluate the long-term effects of developmental exposure in adult animals. Previous work has demonstrated that developmental exposure to benzo[a]pyrene resulted in persistent long-term deficits in adult zebrafish, such as learning and memory during an active avoidance test (Xu et al , 2007; Xu et al , 2012; Truong et al , 2014a; Knecht et al , 2017b). Here, we exposed embryonic zebrafish to both the individual 10 PAHs and SM10 from 6–120 hours post fertilization (hpf) and evaluated morphological and behavioral changes at 120 hpf.…”
Section: Introductionmentioning
confidence: 99%
“…We used the zebrafish model to investigate the toxicity of the individual PAHs compared to the SM10 mixture in developing larvae and to evaluate the long-term effects of developmental exposure in adult animals. Previous work has demonstrated that developmental exposure to benzo[a]pyrene resulted in persistent long-term deficits in adult zebrafish, such as learning and memory during an active avoidance test (Xu et al , 2007; Xu et al , 2012; Truong et al , 2014a; Knecht et al , 2017b). Here, we exposed embryonic zebrafish to both the individual 10 PAHs and SM10 from 6–120 hours post fertilization (hpf) and evaluated morphological and behavioral changes at 120 hpf.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical exposures in adult zebrafish have produced differences in learning and memory retention during an active avoidance test. For example, nitro-L-arginine methyl-ester (L-NAME), (Xu, Scott-Scheiern et al 2007) and methylmercury (Xu, Weber et al 2012) resulted in significantly decreased avoidance and escape responses, reflective of impaired learning. Adult zebrafish developmentally exposed to polybrominated diphenyl ethers (PBDE-47) showed a significantly lower shock avoidance and performance deterioration between a train and test session, suggesting compromised memory in adult animals (Truong, Mandrell et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…While genetic background may account for some of the discrepancy, it is more likely that the differences were methodological. For instance, our use of a 12 s inter trial interval (ITI) was similar to that of Xu et al (Xu et al, 2007, Xu et al, 2012), but Rawashdeh et al used no ITI while Ylieff et al (Ylieff et al, 2008) reported that an 80 s ITI was optimal in Nile tilapia and goldfish when the US shocks were discontinuous (pulsed), but that a 20 s ITI was optimal with continuous shock. The strength of the shock stimulus that we used was based on these same previous reports and adopted by us because a 3 – 5 volt application to the shuttle box elicited a visible escape response from untreated adult zebrafish.…”
Section: Discussionmentioning
confidence: 75%
“…The active avoidance paradigm we reported achieved statistical robustness, and hence confidence in the relative rates of learning among the treatments. However, we acknowledge an important discrepancy with previous studies: While our use of the learner criterion (conditioning to the point of shock avoidance without return to the US side) was insufficient for our analysis due to < 30% of the fish in any treatment meeting the criterion, a similar criterion was met by 60–80% of untreated adult zebrafish fish in two previous studies (Rawashdeh et al, 2007, Xu et al, 2007, Xu et al, 2012). Xu et al initially obtained the 60% metric in pet store zebrafish of unknown lineage and Rawashdeh et al obtained a >80% metric in the common AB strain.…”
Section: Discussionmentioning
confidence: 75%